The Recovery of Energy from a Hybrid System to Improve the Performance of a Photovoltaic Cell - Abdelhak Lekbir; Chin Kim Gan; Mohd Ruddin Ab Ghani; Tole Sutikno (International Journal of Power Electronics and Drive Systems (IJPEDS), 2018)
The main objective of this work is to study a photovoltaic/thermoelectric hybrid generator system, ranging from characterisation of thermoelectric (TE) and photovoltaic (PV) modules basic elements of thermal and PV energy conversion into electrical energy through necessary modelling steps. The bibliographic study allows TE and PV generation to be positioned in the current context, by presenting their history and evolution. In some sectors, this technology has already matured. For example, in the space sector, the scientific activity seems to show an acceleration in hybrid systems development in the solar field. This research field remains completely open, as evidenced by the multiplicity of technological solutions implemented. A significant part of this work has been to develop generic energy models of various modules (PV and thermal) for a multi-source generator design, based on experimental tests and existing technologies. In addition, a methodology for sizing optimisation of such generator was proposed by considering surface or volume criteria, number of thermoelectric generator (TEG) modules and temperature gradient.